Between wife and death - Syuhaidah Azlin (2010)
A young, successful CEO of a large pharmaceutical company, his wife, and her brother attends the CEO's mother-in-law's funeral. Odd behaviour and complications ensue. Throughout the day, the CEO turns fearful, his wife becomes aggressive and her brother gets emotional. Suddenly, complications escelate: Mother has been murdered. As the mystery unravels, so do the characters and another death swings into the picture.